2019
DOI: 10.1038/s41598-019-50135-x
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus infection in people residing in Africa: a systematic review and meta-analysis of prevalence studies

Abstract: Better knowledge of the face of the current dengue virus (DENV) epidemiology in Africa can help to implement efficient strategies to curb the burden of dengue fever. We conducted this systematic review and meta-analysis to determine the prevalence of DENV infection in Africa. We searched PubMed, EMBASE, African Journals Online, and Africa Index Medicus from January 1st, 2000 to June 10th, 2019 without any language restriction. We used a random-effects model to pool studies. A total of 76 studies (80,977 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
97
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 35 publications
12
97
2
3
Order By: Relevance
“…aegypti in relation to dengue fever incidence in Africa. Similarly, other studies also found that in areas with higher temperatures the rate of larval development will increase, which can boost mosquito populations, and increase the probability of eggs being hatched, and thereby increase the dengue fever incidence risk [3,4,6,8,17,19,20,28,39]. At high temperature, the feeding behaviour of the mosquito is also expected to increase, further increasing dengue fever incidence risk [6].…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…aegypti in relation to dengue fever incidence in Africa. Similarly, other studies also found that in areas with higher temperatures the rate of larval development will increase, which can boost mosquito populations, and increase the probability of eggs being hatched, and thereby increase the dengue fever incidence risk [3,4,6,8,17,19,20,28,39]. At high temperature, the feeding behaviour of the mosquito is also expected to increase, further increasing dengue fever incidence risk [6].…”
Section: Discussionmentioning
confidence: 87%
“…aegypti were retrieved from the Global Biodiversity Information Facility (GBIF; www.gbif.org/), VectorMap and scientific publications [3]. Continental sites or areas where dengue was reported were extracted from Simo et al [3] and Messina et al [4]. Several studies only use vector data, i.e.…”
Section: Occurrence Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Last but not the least, conducting HLC raises ethical concerns associated with an increased risk of participants' exposure to infectious mosquito bites if an appropriate anti-malarial chemoprophylaxis is not taken [4,10,16]. The increasing risk of arboviral infections further compounds its limitations [17]. Hence, it may not be practical to deploy HLC for routine malaria vector surveillance.…”
Section: Introductionmentioning
confidence: 99%